Current evidence and clinical relevance of drug-microbiota interactions in inflammatory bowel disease - Becker, Heike E. F.; Demers, Karlijn; Derijks, Luc J. J.; Jonkers, Daisy M. A. E.; Penders, John (Frontiers in Microbiology, 2023)
Background: Inflammatory bowel disease (IBD) is a chronic relapsing-remitting disease. An adverse immune reaction towards the intestinal microbiota is involved in the pathophysiology and microbial perturbations are associated with IBD in general and with flares specifically. Although medical drugs are the cornerstone of current treatment, responses vary widely between patients and drugs. The intestinal microbiota can metabolise medical drugs, which may influence IBD drug (non-)response and side effects. Conversely, several drugs can impact the intestinal microbiota and thereby host effects. This review provides a comprehensive overview of current evidence on bidirectional interactions between the microbiota and relevant IBD drugs (pharmacomicrobiomics). Methods: Electronic literature searches were conducted in PubMed, Web of Science and Cochrane databases to identify relevant publications. Studies reporting on microbiota composition and/or drug metabolism were included. Results: The intestinal microbiota can both enzymatically activate IBD pro-drugs (e.g., in case of thiopurines), but also inactivate certain drugs (e.g., mesalazine by acetylation via N-acetyltransferase 1 and infliximab via IgG-degrading enzymes). Aminosalicylates, corticosteroids, thiopurines, calcineurin inhibitors, anti-tumour necrosis factor biologicals and tofacitinib were all reported to alter the intestinal microbiota composition, including changes in microbial diversity and/or relative abundances of various microbial taxa. Conclusions: Various lines of evidence have shown the ability of the intestinal microbiota to interfere with IBD drugs and vice versa. These interactions can influence treatment response, but well-designed clinical studies and combined in vivo and ex vivo models are needed to achieve consistent findings and evaluate clinical relevance.